Photovoltaic effect and tribovoltaic effect at liquid-semiconductor interface. (May 2021) - Zheng, Mingli; Lin, Shiquan; Tang, Zhen; Feng, Yawei; Wang, Zhong Lin
Abstract: Contact electrification involving semiconductors has attracted attention for that it generates direct current. But its mechanism is still under debate, especially for the liquid-semiconductor cases. Here, the tribo-current is generated by sliding a DI water droplet on a semiconductor wafer, such as Si and TiO2, under the light irradiation. It is revealed that the photoexcited electron-hole pairs at the interface will contribute to the tribo-current, and the enhanced tribo-current increases with the increased light intensity or the decreased light wavelength. The results suggest that the tribo-current at the DI water-semiconductor interfaces is induced by the tribovoltaic effect, in which electron-hole pairs are excited during contact owing to the energy released by the newly formed bonds, which can be named as "bindington". The electron-hole pairs are further driven by the built-in electric field to move from one side to the other side at the interfaces, generating a direct current. The findings imply that the electron transfer exist at the liquid-solid interface in the CE, and support the "two-step" model for the formation of the electric-double layer, which was first proposed by Wang. Graphical Abstract: Contact electrification (CE) is a mysterious natural phenomenon which bewildered human more than 2600 years. One of the most controversial topics is the type of carriers transferred in triboelectricity, either electron transfer or ion transfer especially for solid/liquid CE. Recently, a new theory about the "two-step" model for the formation of electric-double layer (EDL) has been put forward, in which the electron transfer is considered to be the first step. We demonstrate that the tribo-current is generated by sliding a DI water droplet on a semiconductor wafer under the light irradiation. It is revealed that the photoexcited electron-hole pairs at the interface will contribute to the tribo-current. The results suggest that the tribo-current at the DI water-semiconductor interfaces is induced by the tribovoltaic effect, in which electron-hole pairs are excited during friction owing to the energy released by the newly formed bonds, and driven by the built-in electric field to move from one side to the other side at the interfaces, generating a direct current. An energy band model is further proposed, in which the increasing of the electron-hole pairs concentration induced by the photoexcitation is responsible for the enhancement of the tribovoltaic current. The findings imply that the electron transfer exist at the liquid-solid interface in the CE. ga1 Highlights: It is revealed that the photoexcited electron-hole pairs at the interface will affect the tribo-current and tribo-voltage. An energy band model of the couple of tribovoltaic effect and photovoltaic effect is proposed. The findings imply that the electron transfer exist at the liquid-solid interface in the CE.